Regional associations between cerebrovascular disease and cholinergic white matter pathways in the Lewy body continuum - Anna Rennie; Milan Nemy; Cene Jerele; Iñigo Rodríguez-Baz; Victor Montal; Alexandre Bejanin; Milica G Kramberger; Dag Aarsland; Juan Fortea; Alberto Lleó; Eric Westman; Daniel Alcolea; et al. (npj Parkinson's Disease)
Abstract Cerebrovascular disease is common in patients on the Lewy body (LB) continuum (dementia with Lewy bodies (DLB) and prodromal-DLB). White matter signal abnormality (WMSA) volume is higher in patients with LB than controls, both globally and in cholinergic white matter. However, it remains unknown if the higher WMSA in cholinergic white matter reflects selective cholinergic vulnerability or results from higher global WMSA. We modelled cingulate and external capsule cholinergic white matter pathways using MRI and segmented WMSA overlapping cholinergic pathways and per brain lobe. We found that patients on the LB-continuum (n = 33) had higher volume and proportion of WMSA in the cholinergic white matter compared to controls (n = 36), independent of global WMSA. Cholinergic WMSA was associated with neurodegeneration in the basal forebrain, decreased integrity of cingulate and external capsule pathways and attention and memory performance. These findings may suggest a selective vulnerability of cholinergic pathways in patients with LB.